CANOPY RESEARCH METHODS: A REVIEW - heatwole, harold; Higgins, Wayne (Selbyana, 1993)
Forest canopies were long considered to be relatively inaccessible and therefore much neglected as targets for research. The great diversity of organisms there and the complexity ofinteractions among species were suspected but not fully documented. Now, thanks to the developmentofa variety oftechniques permitting reaching and moving within canopies, investigation of this biologically rich area has begun to flourish